EFEKTIVITAS MEDIA KARTU HURUF TERHADAP KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS 1 SD YPK SEGET - Vera Letsia Meres; Roni Andri Pramita; Ahmad Yulianto (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
Early reading instruction is a crucial aspect of developing literacy skills in young children; however, many first-grade students still face difficulties mastering these skills. This study aims to examine the effectiveness of letter card media in enhancing the early reading skills of first-grade students at SD YPK Seget. The method used is a quantitative pre-experimental One Group Pretest-Posttest design, involving 15 students as the sample. Data were collected through pretest and posttest assessments and analyzed using the Paired Samples T-Test with SPSS software. The results show a significant improvement in students' early reading abilities, with the average score increasing from 53.67 to 82.00, and a Normalized Gain value of 0.611 indicating a moderate effectiveness of the media. These findings contribute significantly to the development of adaptive and effective learning media for elementary education and highlight the role of visual media in supporting cognitive processes and student motivation. In conclusion, letter card media is an effective instructional strategy that can be widely implemented, with recommendations for future research to use more complex experimental designs and larger samples for stronger validity.